Enhanced structural properties of In2O3 nanoparticles at lower calcination temperature synthesised by co-precipitation method - Goh, Kian Wei; Johan, Mohd Rafie; Wong, Yew Hoong (Institution of Engineering and Technology, 2018)
Indium oxide nanoparticles (In2O3 NPs) were formed by calcining the optimised as-prepared indium hydroxide (In(OH)3) NPs. The as-prepared In(OH)3 NPs were synthesised at optimal pH 10 through co-precipitation method at various calcination temperatures (200, 300, 400, 500, 600°C) for 2 h. Characterisation of the samples was performed by thermogravimetric (TGA and differential thermal, DTA) analysis, high-resolution transmission electron microscope (HRTEM), X-ray diffractometer (XRD), Fourier transform infrared spectroscopy, and Raman spectroscopy. The complete conversion to In2O3 NPs was reached at 300°C. Besides, the crystallite size of In2O3 NPs calculated by William-Hall equation had the same trend with the values obtained from Scherrer equation. The HRTEM images also showed that the size of In2O3 NPs was within the range of 15-28 nm. Clearly, their work confirmed that the smallest In2O3 NPs (15 nm) with homogenous particle distribution were formed at a lower calcination temperature of 300°C.